1997
DOI: 10.1007/s004250050095
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sucrose and starch metabolism in potato tubers in response to short-term water deficit

Abstract: To investigate the effect of water stress on carbon metabolism in growing potato tubers (Solanum tuberosum L.), freshly cut and washed discs were incubated in a range of mannitol concentrations corresponding to external water potential between 0 and )1.2 MPa. (i) Incorporation of [ 14 C]glucose into starch was inhibited in water-stressed discs, and labeling of sucrose was increased. High glucose overrode the changes at low water stress (up to )0.5 MPa) but not at high water stress. (ii) Although [ 14 C]sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
232
1
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(255 citation statements)
references
References 46 publications
(48 reference statements)
13
232
1
9
Order By: Relevance
“…In response to acute temperature shock, plants mobilize starch at time when biosynthesis would be expected (e.g., in the middle of the light period), resulting in the accumulation of maltose, the major starch catabolite, and of its deriving sugars (Usadel et al, 2008a;Purdy et al, 2013;Guy, 2005, 2004;Sitnicka and Orzechowski, 2014;Yano et al, 2005;Kaplan et al, 2007). Similar rearrangements of starch metabolism are observed when plants are subject to short periods of oxidative or osmotic stress (Scarpeci and Valle, 2008;Zanella et al, 2016;Valerio et al, 2011;Geigenberger et al, 1997). It is proposed that soluble sugars and other charged metabolites, such as proline or glycine, may function as osmoprotectants during stress responses.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In response to acute temperature shock, plants mobilize starch at time when biosynthesis would be expected (e.g., in the middle of the light period), resulting in the accumulation of maltose, the major starch catabolite, and of its deriving sugars (Usadel et al, 2008a;Purdy et al, 2013;Guy, 2005, 2004;Sitnicka and Orzechowski, 2014;Yano et al, 2005;Kaplan et al, 2007). Similar rearrangements of starch metabolism are observed when plants are subject to short periods of oxidative or osmotic stress (Scarpeci and Valle, 2008;Zanella et al, 2016;Valerio et al, 2011;Geigenberger et al, 1997). It is proposed that soluble sugars and other charged metabolites, such as proline or glycine, may function as osmoprotectants during stress responses.…”
Section: Introductionmentioning
confidence: 92%
“…Consistent with this, we observed that osmotic stress caused only a transient decrease in the PSII operating efficiency (FPSII), which was similar in the two genotypes (Supplemental Table 3) and, importantly, did not hinder the capacity of the plants to assimilate 14 CO 2 . However, sugars may also accumulate in leaves because of decreased demand, as a consequence of shoot growth limitation (Hummel et al, 2010), or because of decreased starch biosynthesis (Geigenberger et al, 1997). This might be caused by changes in phosphorylated intermediates, especially 3-phosphoglycerate, reduction of which would inactivate ADP-glucose pyrophosphorylase, the regulated enzyme of starch biosynthesis (Heldt et al, 1977).…”
Section: A Critical Role For Starch Degradation In Osmotic Stress Tolmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotides were determined in the TCA extracts by high pressure liquid chromatography (HPLC) (Geigenberger et al, 1997), using a Kontron HPLC system (Kontron Instruments, Eching, Germany) fitted with a Partisil-SAX anion exchange column (Knauer, Berlin, Germany). An aliquot of the TCA extract (250 µl) was freeze-dried and re-dissolved in a volume of 50 µl, from which 20 µl was injected.…”
Section: Determination Of Nucleotidesmentioning
confidence: 99%
“…No entanto, a maioria deles utiliza como modelo espécies de interesse agronômico, tais como milho (Sharp & Lenoble 2002, Sharp et al 2004, Fan & Neumann 2004, trigo (Asseng et al 1998, Morillon & Lassalles 2002, Piro et al 2003, grão-de-bico (Basu et al 2007), mandioca (Santisopasri et al 2001) e batata (Geigenberger et al 1997). Especifi camente no caso da batata (Solanum tuberosum L.), que acumula amido como principal carboidrato de reserva em seus órgãos subterrâneos (tubérculos) e também uma das mais estudadas sob condições de estresse hídrico, os trabalhos realizados demonstram que a disponibilidade hídrica regula as taxas de síntese de amido e crescimento dos tubérculos (Oparka & Wright 1988a, b) e que tanto a síntese como a degradação desse carboidrato são alteradas sob condições de déficit hídrico, com respostas, em geral, associadas ao aumento nos níveis de açúcares solúveis e inibição da síntese de amido (Geigenberger et al 1997). De acordo com esses autores, a direção da via metabólica para síntese de sacarose ou amido representam uma estratégia importante sob condições de défi cit hídrico, visto que infl uenciam a regulação do potencial osmótico interno, das relações hídricas e, por extensão, do crescimento da planta.…”
unclassified